Childhood Reflected In Martin Scorsese's Hugo Movie (2011):An Individual Psychological Approach - Tirafiah, Octria, Dr. Phil. Dewi Candraningrum, S.Pd., M. Ed, Drs. Abdillah Nugroho, M. Hum (2013)
This study is aimed to show how childhood in Hugo movie by using individual psychological approach. It is done by determining two objectives: the first is analyzing the movie based on its structural elements and the second is analyzing the movie based on the Individual Psychological Approach. This research is descriptive qualitative research. Type of data of the study is text and image taken from two data sources: primary and secondary. The primary data source is Hugo movie directed by Martin Scorsese released in 2011. Whereas the secondary data sources are other materials taken from books or e-books, journals, internet related to the study. They are collected through library study and analyzed by descriptive analysis. The study draws the following conclusions. Firstly, based on the structural analysis of Hugo movie expressed the message that children solve problem through their adventure and a toy could influence for their development as an active child. The structural elements are linked to each other in unity. Secondly, based on Individual Psychological analysis reflected in the character and characterization in inferiority feeling and compensation, striving for superiority, fictional finalism, style of life, social interest, and creative self, the power of child's personality in solving a problem and the role of toy in building the developmental of child.